Leaching of a low-grade, copper-nickel sulfide ore. 1. Key parameters impacting on Cu recovery during column bioleaching - Watling, Helen; Elliot, A.; Maley, Mark; Van Bronswijk, Wilhelm; Hunter, C. (Elsevier Science BV, 2009)
This study was prompted by the disparate recoveries of nickel (>70%) and copper (<20%) from a test heap of copper-nickel sulfide ore after about 200 days of leaching. Variables tested in bioleaching columns charged with a pyrrhotite-rich, chalcopyrite and pentlandite ore were acid pre-conditioning, inoculation and aeration. The results indicated that the rapid reaction of pyrrhotite with acid created conditions that impacted directly and/or indirectly on copper recovery. Important reactions were hydrogen sulfide formation, high soluble iron concentrations and the formation of large amounts of elemental sulfur. It was hypothesized that copper loss, evidenced by copper re-distribution during passage through the ore, was mainly the result of reaction with hydrogen sulfide to form covellite, although this could not be confirmed by XRD analysis of leached residues. A layer of iron-oxy-hydroxy-sulfate 'scale' on particle surfaces encapsulated sulfide grains as well as elemental sulfur formed by the oxidation of pyrrhotite and was of sufficient depth and integrity to have hindered but not prevented leaching and bioleaching. Lack of aeration (oxygen, carbon dioxide) impacted on ferrous ion biooxidation and probably sulfur biooxidation. More extensive sulfur biooxidation to form acid might have lowered the solution pH and reduced the amount of scale formation, resulting in higher ferric ion concentrations and better chalcopyrite oxidation.